Aplikasi Sistem Resirkulasi Filtrasi Pada Pendederan Ikan Lele Sangkuriang (Clarias sp) di Bak Terpal Bagi Kelompok Pembudidaya Ikan Tani Makmur Di Desa Punggur Kabupaten Kubu Raya - Ridwan Salim; Farid Mudlofar; Rizal Akbar Hutagalung; M. Taufik (Politeknik Negeri Pontianak, 2021)
Sangkuriang catfish is one of the superior catfish strains that has high economic value by means of fish breeding which is relatively easy, but the availability of water has decreased quality in the cultivation process, so the necessity of the application of filtration recirculation system in order to maintain the quality and quantity of water in order to support the growth rate and survival rate in the nursery process of sangkuriang catfish. Problems faced by the Farmers Farmers' Group Makmur in the Punggur Kecil Village, especially in implementing sangkuriang catfish nursery with a recipe system, of course, technically the community does not master because they are accustomed to gardening even though there are some farmer groups that have pondered fish but the knowledge about fish farming is good and right of course the knowledge of knowledge is still limited, in order to overcome the problem, it is necessary to have counseling from universities to transfer fisheries cultivation technology by means of assistance so that the community can independently carry out fish farming activities with the reculation system. The activities in the application of science and technology include socialization activities, counseling, science and technology applications in fish culture to technical and business evaluations and assistance during the process of fish farming activities. The technical results obtained by fish farmers during sangkuriang catfish breeding with a filtration recirculation system are with a significant increase in growth rate and survival rate during maintenance reaching 86.15%, from the evaluation of the technical results based on the value of community welfare where profits are obtained the increasing business feasibility and feasibility in terms of the B / C ratio <1 so that it is expected to have an impact on increasing profits in raising sangkuriang catfish. Keywords: Breeding, Sangkuriang catfish , Recirculating, Filtration, Punggur Village